1998
DOI: 10.5632/jila.61.325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Urbanization on the Performance of the Home Gardens in West Java, Indonesia

Abstract: The home garden "peharangan" in Indonesia is the traditional garden with agroforestry and sustainable land use in the tropical regions. The objective of the present study was to elucidate the effects of urbanization on the performance of the home gardens in West Java, Indonesia.The study sites were ranked into the least urbanized site, the intermediate urbanized site, and the most urbanized site. The performances of the home gardens were compared among these different urbanized sites. The home gardens in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 3 publications
0
24
0
5
Order By: Relevance
“…The number of species in a pekarangan varied from place to place according to the local physical circumstances, the ecological characteristics of the plants, animal species, socioeconomic factors, and cultural factors (Abdoellah 1991). Arifin (1998) and Arifin et al (1998) showed that the number of plant species present varied widely among the (Table 2). Mean species number per pekarangan did not differ markedly between the rural, intermediate and urban pekarangans.…”
Section: Metropolitan Jakartamentioning
confidence: 97%
“…The number of species in a pekarangan varied from place to place according to the local physical circumstances, the ecological characteristics of the plants, animal species, socioeconomic factors, and cultural factors (Abdoellah 1991). Arifin (1998) and Arifin et al (1998) showed that the number of plant species present varied widely among the (Table 2). Mean species number per pekarangan did not differ markedly between the rural, intermediate and urban pekarangans.…”
Section: Metropolitan Jakartamentioning
confidence: 97%
“…Herbaceous plants, such as vegetables, starchy crops, and spice plants, are seasonal plants that are highly affected by climatic parameters, such as rainfall and temperature, and they are easily accessed through the market for subsistence consumption. On the other hand, when considering economic aspects, ornamental species are more attractive for households than vegetables due to the market economy in urbanized areas in particular [14,19,34,[45][46][47][48].…”
Section: Sustainable Management Of Home Gardens In West Java Indonesiamentioning
confidence: 99%
“…However, households are not able to generate income by fruit selling throughout the year, since fruit production is seasonal, and dependent on the climate and healthy tree conditions. In this case, ornamental plants are able to alternatively provide sustainable income for households as well as aesthetic function in response to urbanization [45]. Ornamental plants are used to plant in the space between houses as a fence to emphasize aesthetic function with medicinal plants and clove trees [39].…”
Section: Sustainable Management Of Home Gardens In West Java Indonesiamentioning
confidence: 99%
“…Pekarangan yang ekologis terdiri dari keragaman strata vegetasi. Menurut Arifin (1998), keragaman strata dibagi kedalam lima strata ketinggian. Strata I merupakan tanaman dengan ketinggian yang kurang dari 1 m seperti rumput dan herba, strata II merupakan tanaman dengan ketinggian antara 1-2 m seperti semak, strata III adalah tanaman yang memiliki ketinggian antara 2-5 m seperti perdu dan pohon kecil, tanaman dengan strata IV memiliki ketinggian 5-10 m seperti pohon sedang, dan pohon tinggi dengan ketinggian di atas 10 m dikelompokan dalam strata V.…”
Section: Pekaranganunclassified